Enhancing early warning: A DNA biosensor with polyaniline/graphene nanocomposite for label-free voltammetric detection of saxitoxin-producing harmful algae - Chwan Chuong Chin, Jeremy Jason; Akbar, Muhamad Afiq; Mohd Yusof, Nurul Yuziana; Pike, Andrew; Goh, Choo Ta; Mustapha, Shuhadah; Tan, Ling Ling (Elsevier, 2024)
Yearly reports of detrimental effects resulting from harmful algal blooms (HAB) are still received in Malaysia and other countries, particularly concerning fish mortality and seafood contamination, both of which bear consequences for the fisheries industry. The underlying reason is the absence of a dependable early warning system. Hence, this research aims to develop a single DNA biosensor that can detect a group of HAB species known for producing saxitoxin (SXT), which is commonly found in Malaysian waters. The screen-printed carbon electrode (SPCE)-based DNA biosensor was fabricated by covalent grafting of the 3’ aminated DNA probe of the sxtA4 conserved domain in SXT-producing dinoflagellates on the reverse-phase polymerized polyaniline/graphene (PGN) nanocomposite electrode via carbodiimide linkage. The introduction of a carboxyphenyl layer to the PGN nanotransducing element was essential to augment the carboxylic groups on the graphene (RGO), facilitating attachment with the aminated DNA. The synergistic effect of the asynthesized nanocomposite of PANI and RGO, tremendously enhanced the electron transfer rate of the ferri/ferrocyanide redox probe at the SPCE transducer surface, allowing for the label-free bioanalytical assay of complementary DNA targets. The developed DNA biosensor featuring the capacity to detect a broad range of Alexandrium minutum (A. minutum) cell concentrations, ranging from 10 to 10,000,000 cells L-1. The quantification of A. minutum cells from pure algal culture by the electrochemical DNA biosensor has been well-validated with traditional microscopic techniques. Furthermore, Alexandrium tamiyavanichii, another toxigenic HAB species, exhibited a similar electrochemical characteristic signal to those observed with A. minutum, whilst the biosensor yielded appreciably distinctive results when subjected to a non-toxigenic microalgae species as a negative control, i.e. Isochrysis galbana. A compendium DNA biosensor design and electrochemical detection strategy at laboratory scale serves as a precursor to the potential development of portable device for on-site detection, thus expanding the utility and scope of biosensor technology. © 2024 Elsevier Ltd